Marketing Ethics At Islamic Banks: Principles And Practices - M Qoshid Al Hadi; Eko Nur Cahyo; Iman Setya Budi (Journal of Islamic Economic Laws, 2021)
This article highlights the principles and implementation of Islamic banking marketing ethics. Ethics based on sharia principles are an essential differentiator from their competitors. It begins from the 4 P's marketing mix framework, namely product, price, promotion, and place. This article is qualitative descriptive research using literature review. This article employs secondary data from 11 articles. The data that has been collected then analyzed with descriptive information. Therefore, through 4 P's marketing mix lens, this article finds a lack of ethical marketing practices in Islamic Banking from the ethical ideals espoused in the literature. This study analyzes the ethical marketing practices of Islamic banks which can be used as an evaluation of policies in the Islamic financial industry.